Influence Of Human Development Index, Foreign Investment, Labor Force And Money Supply On GDP In Selected ASEAN Countries - Dimas Bagus Wiranatakusuma; Imamudin Yuliadi; Natania Syafiqur Rahma (UNIVED Press, 2025)
Gross Domestic Product (GDP) is a very important indicator in analyzing economic developments that occur in a country. GDP shows the extent to which economic activities will generate additional income for society within a certain period. This research aims to analyze the factors that influence the GDP of several selected ASEAN countries for the 2012-2021 period. The dependent variable used is GDP while the independent variables are the Human Development Index, Foreign Investment, Labor force and Money Supply. The data used in this research is collected from valid secondary sources, namely the official World Bank website. The analytical method used in this research is multiple linear regression analysis by using EViews 7 software. The research results show that the Human Development Index has a positive and insignificant effect on GDP. Then Foreign Investment has a positive and significant effect on selected ASEAN GDP. Then the total number of workers has a positive and significant effect on GDP. However, the Money Supply has a negative and significant effect on selected ASEAN countries. Therefore, the government should enhance human development by improving education and health services, infrastructure, innovation, and research. To boost GDP, ASEAN countries should attract foreign investment and improve human resource quality through education, training, and experience. Additionally, the government should control and stabilize the money supply to prevent excessive inflation and recession in ASEAN countries.